2014
DOI: 10.3390/soc4020161
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Hard Martial Arts in People over Forty: An Attempted Systematic Review

Abstract: Abstract:The objective was to assess the effect of hard martial arts on the physical fitness components such as balance, flexibility, gait, strength, cardiorespiratory function and several mental functions in people over forty. A computerized literature search was carried out. Studies were selected when they had an experimental design, the age of the study population was >40, one of the interventions was a hard martial art, and when at least balance and cardiorespiratory functions were used as an outcome measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
4
0
2
Order By: Relevance
“…The intervention study sought to explore the impact of Tai Chi on prevalence of further falling and found that there were statistically significant beneficial differences in the rate of falls for the Tai Chi experimental group (Hwang, Chen, Lee-Hsieh, Chien, Chen and Lin, 2016). Despite a growing body of evidence however, Pons van Dijk, Leffers and Lodder (2014) note that some of the underpinning methods of the published research are less than rigorous. On a more encouraging note though, they add that the suggestive themes emerging from their attempted systemic review of published research does point positively to benefits, and thus conclude by highlighting the important need of carrying out more research.…”
Section: Eastern Philosophy and Its Relevance To Martial Artsmentioning
confidence: 99%
“…The intervention study sought to explore the impact of Tai Chi on prevalence of further falling and found that there were statistically significant beneficial differences in the rate of falls for the Tai Chi experimental group (Hwang, Chen, Lee-Hsieh, Chien, Chen and Lin, 2016). Despite a growing body of evidence however, Pons van Dijk, Leffers and Lodder (2014) note that some of the underpinning methods of the published research are less than rigorous. On a more encouraging note though, they add that the suggestive themes emerging from their attempted systemic review of published research does point positively to benefits, and thus conclude by highlighting the important need of carrying out more research.…”
Section: Eastern Philosophy and Its Relevance To Martial Artsmentioning
confidence: 99%
“…Older adults reinforce their social identity through participating in sport, use sport to differentiate themselves from non-active older adults or use sport as a mechanism to transform their identity from an ageing older adult to a competitive athlete 20 . Considering, for example, the sport of martial arts, always more older adults enjoy the practice and join them 21 .…”
Section: Sport and Elderly Peoplementioning
confidence: 99%
“…Las diferentes AM&DC tienen características específicas, clasificadas en dos grandes grupos: AM&DC 'duras' o 'externas' y AM&DC 'blandas' o 'internas' (2). Las AM&DC 'internas', como el tai chí, se caracterizan por movimientos suaves y relajados que a menudo se ejecutan lentamente; apuntando a la regulación de la postura durante la ejecución de sus movimientos.…”
Section: Sra Editora Revista Hacia La Promoción De La Saludunclassified
“…Por su parte las AM&DC 'externas' se caracterizan por movimientos rápidos, vigorosos y dinámicos dirigidos a generar y transmitir la máxima fuerza posible a la superficie de ataque (2). Hoy en día, las investigaciones sobre los efectos que las AM&DC 'externas' pueden tener sobre la salud se encuentran en aumento; existiendo estudios sobre el equilibrio, fuerza muscular, densidad mineral ósea, cognición, entre otros, en distintos grupos de la población (2).…”
Section: Sra Editora Revista Hacia La Promoción De La Saludunclassified